MOTIVASI KERJA DALAM MEMBUAT KRIPIK BALADO MELALUI BANTUAN TUTOR SEBAYA PADA ANAK TUNAGRAHITA RINGAN KELAS V DI SDLB PAINAN - MISWARDI - MISWARDI (Jurnal Penelitian Pendidikan Khusus, 2012)
Abstract This study removed using action research method (Classroom Action Research) conducted in collaboration with colleagues. Data collected through observation techniques, and tests, and then analyzed qualitatively andquantitatively The results showed that peer assistance in making chips Balado through two cycles. Each Five meetings were held for the first cycle and four for the second cycle that began with the beginning, the core activities and the final activity showed good success. The assessment (initial test) the ability of WS (33.3%), FD (19%) ID (19%) and YS (4.7%). Cycle I WS gets results (81%), FD (77%), MY (51.4%) and YS got value (38.1%). In the second cycle WS scored (100%), FD got (94%), MY scored (89.3%) and YS mndapat value (80%) This shows the increase and success after extensive repairs, and the role of peers in helping make the chips balado.Maka suggested to teachers in teaching skills to children Tunagrahita Lightweight better students who are able / completion to help a friend who has not completed (peer tutoring), so that children are able to independently light Tunagrahita either within the family or within the community , and can live well with good economy thanks to possess skills that can ensure their future. Kata kunci       : Tunagrahita Ringan, bantuan tutor sebaya, hasil pembuatan kripik balado